HAND DOLL MEDIA DEVELOPMENT FOR IMPROVING THE ABILITY OF STORY BACK FOR CLASS II SDN 1 SOMBRON - Fitri Puji Astutik; Eko Handi Winarko (PROGRES PENDIDIKAN, 2022)
The students' storytelling ability after using hand puppet media, the material retells the children's stories that were heard using the second grade students' own words. The validity, practicality, and effectiveness of the hand puppet media were used in the material for retelling children's stories that were heard using the second grade students' own words. This study uses a research development (R & D) procedural model with Borg and Gall development procedures. The research subjects were 31 students of class II SDN 1 Sombron, Kediri, by giving tests to students through pretest and posttest research techniques by providing instruments in the form of 4 psychomotor test questions, namely storytelling. The conclusions of this study are: (1) The process of developing hand puppet media is easy to do with creativity and new innovations to make it look more attractive to students. (2) The ability of students to retell the story they have heard using their own words after using hand puppet media increases. The results of the pretest obtained an average score of 81.2 students, while from the posttest results the average score of students was 86.8 (there was an increase of 5.6). From the test results, it can be said that the use of hand puppet media is effectively used in Indonesian language lessons with the material of retelling children's stories that are heard using their own words because students are more active and enthusiastic in learning activities. (3) Validation carried out by material experts and media experts got a score of 85.285% so that it can be stated that the development of hand puppet media is very valid, very effective, very complete, can be used without improvement.